Theoretical Systematization of Research Competence - Odiel Estrada Molina (Universidad Nacional, Costa Rica, 2014)
This paper constitutes a literature review that evidences that competency acquisition in higher education has boomed in the XXI century and that one of the competencies developed is research. The objective of this paper is to prepare a theoretical systematization of the years 1999-2013 using the existing research projects regarding the acquisition and development of research competence in higher education, based on its concept and the relationships between each of its components and dimensions. The research methods used were historical-logical and analytic-synthetic and the technique used was the document analysis of 40 papers by authors from Europe, Asia and the Americas. The paper presents a pedagogical analysis of the results obtained, identifies strengths and weaknesses, and proposes a number of pedagogical considerations to be included in the acquisition and development of this competence. The main result obtained is that neither a professional nor a technological component has been fully integrated to the research competence structure.